Impact of mechanical bowel preparation in elective colorectal surgery: a meta-analysis - Rollins, Katie E; Javanmard-Emamghissi, Hannah; Lobo, Dileep N. (Baishideng Publishing Group, 2018)
AIM: To analyse the effect of mechanical bowel preparation vs no mechanical bowel preparation on outcome in patients undergoing elective colorectal surgery. METHODS: Meta-analysis of randomised controlled trials and observational studies comparing adult patients receiving mechanical bowel preparation with those receiving no mechanical bowel preparation, subdivided into those receiving a single rectal enema and those who received no preparation at all prior to elective colorectal surgery. RESULTS: A total of 36 studies (23 randomised controlled trials and 13 observational studies) including 21568 patients undergoing elective colorectal surgery were included. When all studies were considered, mechanical bowel preparation was not associated with any significant difference in anastomotic leak rates (OR = 0.90, 95%CI: 0.74 to 1.10, p = 0.32), surgical site infection (OR = 0.99, 95%CI: 0.80 to 1.24, p = 0.96), intraabdominal collection (OR = 0.86, 95%CI: 0.63 to 1.17, p = 0.34), mortality (OR = 0.85, 95%CI: 0.57 to 1.27, p = 0.43), reoperation (OR = 0.91, 95%CI: 0.75 to 1.12, p = 0.38) or hospital length of stay (overall mean difference 0.11 d, 95%CI: -0.51 to 0.73, p = 0.72), when compared with no mechanical bowel preparation, nor when evidence from just randomized controlled trials was analysed. A sub-analysis of mechanical bowel preparation vs absolutely no preparation or a single rectal enema similarly revealed no differences in clinical outcome measures. CONCLUSION: In the most comprehensive meta-analysis of mechanical bowel preparation in elective colorectal surgery to date, this study has suggested that the use of mechanical bowel preparation does not affect the incidence of postoperative complications when compared with no preparation. Hence, mechanical bowel preparation should not be administered routinely prior to elective colorectal surgery.